The pliomerid trilobite Ibexaspis and related new genera, with species from the Early Ordovician (Floian; Tulean, Blackhillsian) of the Great Basin, western USA - Mcadams, Neo E.b.; Adrain, Jonathan M.; Karim, Talia S. (Zootaxa, 2018)
Field-based revision and phylogenetic analysis demonstrate that the pliomerid trilobite taxon Ibexaspis Přibyl and Vaněk (in Přibyl et al., 1985), previously known from a single formally named species (I. brevis [Young, 1973]), belongs to a complex of 14 mostly newly discovered, related species from the Early Ordovician (Floian; Tulean and Blackhillsian) of the northern Laurentian margin. The species are known from silicified samples recovered from sections in eastern Nevada, western Utah, and southeastern Idaho. The stratigraphically early Tuleaspis n. gen. (type species: T. jeneki n. sp.; Tulean; low Protopliomerella contracta Zone) includes its type and two species described in open nomenclature. Tuleaspis is sister to the remainder of the clade. Ibexaspis now includes three additional species: I. coadyi n. sp. (Blackhillsian; Carolinites nevadensis Zone), I. leuppi n. sp. (Blackhillsian; Presbynileus ibexensis Zone), and I. rupauli n. sp. (Blackhillsian; "Pseudocybele nasuta Zone"). Ibexapsis is sister to a clade of Millardaspis n. gen. + Deltapliomera n. gen. Millardaspis (type species M. milsteadi n. sp.; Tulean; Heckethornia hyndeae Zone) also includes M. knoxi n. sp. (Tulean; Panisaspis sevierensis Zone). Deltapliomera (type species D. humphriesi n. sp.; Blackhillsian, Carolinites nevadensis Zone) also includes D. inglei n. sp. (Tulean; Heckethornia bowiei Zone), D. heimbergi (Tulean; Panisaspis sevierensis Zone), D. eppersoni n. sp. (Blackhillsian; Bathyurina plicolabeona Zone), and a species described in open nomenclature.